Taxation in Sub-Saharan Africa - Tanzi, Vito (Occasional Papers; Occasional Paper ;, 1981)
This study indentifies some of the taxation problems most frequently encountered by Fund member countries in sub-Saharan Africa and seeks solutions that may be useful to either the region as a whole or to groups of countries in the region.